Enhancement of nasal and intestinal calcitonin delivery by the novel Pheroid™ fatty acid based delivery system, and by N-trimethyl chitosan chloride - du Plessis, L.H.; Lubbe, J.; Strauss, T.; Kotzé, A.F. (International journal of pharmaceutics, 2010)
Therapeutic peptides are highly potent and specific in their functions, but difficulties in their administration require parallel development of viable delivery systems to improve their bioavailability. In this study the potential of a novel lipid-based colloidal delivery system for improving the absorption of nasally and intestinally administered salmon calcitonin (sCT) was investigated. Two types of delivery vehicles based on Pheroid™ technology was prepared and characterized. Liposome-like bilayer vesicles had a mean diameter of 1.0 μm and microsponges were 1.6 μm. Doses of 10 IU/kg and 500 IU/kg bodyweight sCT were administered intranasally and intestinally to rats, respectively. The obtained absorption enhancement with Pheroid™ vesicles and Pheroid™ microsponges were also compared with the absorption enhancement obtained with N-trimethyl chitosan chloride (TMC). With the inclusion of 0.5% (w/v) TMC the maximum plasma concentration ( C max) of sCT increased from 72.6 ± 6.1 pg/ml to 478.5 ± 6.1 pg/ml after nasal administration. Pheroid™ vesicles and Pheroid™ microsponges increased the C max values of sCT to 262.64 ± 17.1 pg/ml and 202.66 ± 28.6 pg/ml, respectively. The time to reach the maximum concentration ( T max) was also significantly decreased from 35 min to approximately 14 min. Intestinal administration of Pheroid™ formulations increased the C max of sCT from 249.1 ± 21.5 pg/ml to 386.2 ± 45.5 and 432.1 ± 18.9 pg/ml, respectively for Pheroid™ vesicles and Pheroid™ microsponges. TMC increased the C max of sCT to 738.9 ± 277.1 pg/ml. TMC and Pheroid™ technology could offer the potential to significantly improve intranasal and intestinal absorption of sCT and reduce the variability in absorption.